IMMUNODIAGNOSIS OF TUBERCULOSIS USING PCR AND BCG VACCINE BASED ELISA TECHNIQUE - S. Nath, Sooraj (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Tuberculosis causes immense consequences on society. One person out of three is infected with M. tuberculosis and accounts for about 2 billion worldwide. Diagnosis of tuberculosis (TB) remains an enigma despite many technological developments. The main purpose of this study is to develop a diagnostic tool which can yield results within short period of time and much higher sensitivity rate. In this study, 200 serum samples were used for developing ELISA by using BCG strain as source of diagnostic antigen. Out of 200 assayed serum samples, 149 samples gave positive results with the sensitivity rate of 88.7%. Keywords: BCG, tuberculosis (TB), sonicate antigen, culture filtrate antigen, ELISA, PCR.